Pengembangan Video Tutorial Gerak Dasar Tangan dan Kaki pada Mata Kuliah Senam Irama - Wijaya, I Gusti Putu Aldipa Putra; Darmayasa, I Putu; Spyanawati, Ni Luh Putu; Astra, I Ketut Budaya; Satyawan, I Made (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop video tutorial-based learning media on the material of basic hand and foot combination movements in the Rhythmic Gymnastics and Fitness Learning TP course. The research method uses the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. Product validation was carried out by material experts, instructional design experts, media experts, and field practitioners to assess the feasibility of the developed media. Product trials involved students of the Physical Education, Health, and Recreation Study Program through individual, small group, and large group testing stages. Data collection techniques were carried out using a questionnaire with a Likert scale, while data analysis used qualitative and quantitative descriptive approaches. The results showed that the assessment from material experts obtained a percentage of 90%, design experts 94.3%, media experts 100%, and field practitioners 90% with a very good category. In addition, the results of individual trials obtained a percentage of 93.3%, small group tests 90%, and large group tests 90%, all of which were in the very good category. In conclusion, the developed video tutorial-based learning media is deemed suitable for use as a learning resource and effective as a supporting medium in rhythmic gymnastics and fitness lectures. Keywords: ADDIE, Development, Physical Education, Rhythmic Gymnastics, Video Tutorial